Large Area Growth and Phase Selectivity of MoTe2 Nanosheets through Simulation‐Guided CVD Tellurization. Issue 1 (25th October 2022) - Tummala, Pinaka Pani; Ghomi, Sara; Casari, Carlo Spartaco; Martella, Christian; Lamperti, Alessio; Molle, Alessandro
Abstract: Among transition metal dichalcogenides, molybdenum ditelluride (MoTe2 ) holds significant attention due to its polymorphic nature including semiconducting, metallic, and topological semimetal phases. Considerable efforts are devoted to synthesizing MoTe2 nanosheets to make them suitable for device integration in nanotechnologies and for fundamental investigations. In this respect, chemical vapor deposition (CVD) via tellurization of a pre‐deposited Mo thin film is an easy and flexible way for synthesizing large scale MoTe2 nanosheets. Here, the study report on the CVD of large‐area (up to 4 cm × 1 cm) MoTe2 nanosheets with pure 1T' and 2H phase selection by design. Within the tellurization scheme, the vapor‐solid reaction between the pre‐deposited molybdenum film and tellurium vapor is studied thus optimizing the scalability and quality of the MoTe2 nanosheets grown on SiO2 /Si substrates. It is demonstrated that the MoTe2 structure and morphology are kinetically dictated by the tellurium concentration gradient on the reaction site with varying geometric configurations inside the CVD reactor. This study provides a pivot scheme for enabling scalable 1T' and 2H‐MoTe2 integration in applications for novel micro‐ and nano‐electronics, spintronics, photonics, and thermoelectric devices. Abstract : A synergistic use of finite element simulations as a guide together with tellurization process by chemical vapor deposition allows to evidence the key role of tilt angle and distribution of Te vapor concentration gradient at the substrate position in the reactor to obtain molybdenum ditelluride few‐layer nanosheets on large area growth and phase selectivity, namely pure 1T' or 2H phase.